Unravelling chain confinement and dynamics of weakly entangled polymers in one component nanocomposites - Kruteva, M.; Monkenbusch, M.; Sharma, A.; Allgaier, J.; Hoffmann, I.; Rosi, B.; Dulle, M.; Porcar, L.; Matsarskaia, O.; Richter, D. (Soft Matter, 2025)
Structure and dynamics of polymer chains grafted to a nanoparticle (NP) surface in one component nanocomposites (OCNC) are investigated by small angle scattering (SAXS, SANS) and neutron spin echo (NSE). The OCNC were realized by self-assembly of block-copolymers and subsequent cross-linking of the core. The sizes of the resulting NPs were narrowly distributed. Owing to equal core and shell volumes the melt structure is that of a concentrated colloidal dispersion of cores. The melt structure could be reasonably well described by a Percus-Yevick structure factor. In order to access more deeply the dynamics, three differently labeled materials with labels at the inner- or outer part and the whole graft were studied. The experimental data were evaluated in terms of models allowing for site dependent friction. For this purpose, the Langevin equation containing a friction profile was solved and the dynamic structure factor in terms of its eigenvalues and eigenvectors was compared to the data. The evaluation shows increased friction towards the grafting points. In addition, topological restrictions of motion due to the dense arrangements of micellar cores and the presence of neighboring chains were considered and compared with those of a corresponding melt. Assuming homogenous relaxation of all grafts did not yield a satisfactory data description, but rather at least two differently relaxing chain ensembles had to be considered.